Simple and non-charged long-lived fluorescent intracellular organelle trackers. (December 2020) - Herrero-Foncubierta, Pilar; González-García, María del Carmen; Resa, Sandra; Paredes, Jose Manuel; Ripoll, Consuelo; Girón, Maria D.; Salto, Rafael; Cuerva, Juan M.; Orte, Angel; Miguel, Delia
Abstract: In this work the preferential accumulation of long-lived acridone derivatives in mitochondria were evaluated, based on a new concept of non-protonable and non-charged group carriers. In this sense, the thiophene ring has been proved to act, for the first time, as mitochondria targeting group. Moreover, the unique long lifetime of the dyes has allowed the determination of the polarity of the organelles by fluorescence lifetime imaging microscopy (FLIM), without causing remarkable cytotoxicity. The neutral nature of the vectoring group favors the synthetic process and prevents the modification of different organelle parameters as membrane potential, making these probes excellent candidates to organelle tracking. Graphical abstract: Image 1 Highlights: Thiophene ring acts as unreported non-charged mitochondrial targeting group. Long-lived fluorescent probes allow polarity determination inside mitochondria and lysosomes. Co-localization in organelles has been analyzed with FLIM microscopy taking advantage of time-gated technique.